PENGARUH PADA HARGA, KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI IMELDA PONSEL TELUK DALAM - Laia, Septiani (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This research was conducted to determine the effect of price and service quality on consumer satisfaction at Imelda Mobile Teluk Dalam. The way to carry out this research is by using quantitative methods, which are methods of management and calculations carried out in detail. The type of research data used in this research is primary data. Based on the results obtained that. In terms of the regression equation, we obtain a number of values and influences on each variable where Y ̂= 1.922+ .552X1+.413X2 which is all the variables that have an influence on each variable. There is a suggestion for this research that each variable should pay more attention and maintain existing indicators. In order to further increase progress in consumer satisfaction that occurs at Imelda stores.